Readiness for Blended Learning viewed from the Students Attitude towards Learning Aspects - Yulia, Hanita (International Journal of Active Learning, 2017)
Blended Learning combines the advantages of online learning and conventional classroom. However, merely combining online learning and conventional classroom might not fulfill students need, and could lead to unexpected failure. Therefore, it is necessary to know the students readiness, which is a prerequisite for the successful implementation of this learning model. This is a qualitative and quantitative descriptive research, aims to describe the students readiness for Blended Learning implementation, viewed from the students attitude towards learning aspects in Blended Learning. The questionnaires were distributed to 108 students of the Faculty of Information and Technology to know the use of technology, internet access, online activities, and the students attitude toward learning aspects. In-depth interviews to the students were conducted to know deeper on the students attitude toward the learning aspects in BL. The findings show that the students were very ready for the implementation of Blended Learning. It can be seen from students positive atitude toward online aspects (learning flexibility, online learning, online interaction, and study management), as much as 83%, higher that the score of their attitude toward conventional classroom learning which is 77%. The studentsreadiness is a foundation for the successful implementation of Blended Learning, which should be supported by both lecturers and organization.